Permasalahan Kependudukan di Provinsi Kalimantan Selatan - Nur Falikhah (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Population control remains a major agenda for both the Indonesian government and the province of South Kalimantan. Based on the results of the population projections population increased significantly. In addition to issues of quantity, issues such as the quality of population, unbalanced population distribution is and incomplete population database are the focus of the government to increase the welfare of its inhabitants. These four issues of population are the focus of both the central government and other provinces in Indonesia. To overcome them the South Kalimantan provincial government must be smart because of the high quantity of its population, the population continues to increase due to the habit of marriage at an early age. Plus the age composition of the population of South Kalimantan is a group of young people. This is of course a supporting factor of birthrate. For that we need cooperation between several parties. Not only the government sector alone, non- government organizations also need to be included to jointly control the number of residents in the province of South Kalimantan.